Climate change and event uncertainty in a dynamic model with overlapping generations - Michele Moretto; Roberto Tamborini (Fondazione Eni Enrico Mattei (FEEM), 1997)
In this paper the climate change effect is an unforeseen earth temperature level above which a negative externality on technology and hence on society's welfare is exerted. We use a dynamic overlapping generations model to develop a positive analysis of the growth path of an economy with the negative temperature spillover leading to a structural breakdown in capital productivity. Two scenarios for the impact of climate change on intergenerational equity are analyzed: the first is consistent with a state-of-nature framework in which atomistic agents cannot influence the probability that a particular event (productivity collapse) will occur. In the second, according to the maxim "that everybody does what I am doing...«, agents recognize that their choices may influence the probability of productivity collapse occurring in their lifetime.
Keywords: C61; D81; Q25; 330; Global Warming; Event Uncertainty; Overlapping Generations; Klimawandel; Overlapping Generations; Risiko; Dynamisches Gleichgewicht; Theorie